2018
DOI: 10.1016/j.jcrs.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Phacoemulsification and endocyclophotocoagulation in uncontrolled glaucoma: Three-year results

Abstract: At 3 years postoperatively, combined cataract surgery and 360-degree ECP achieved a modest but significant drop in IOP in phakic patients with uncontrolled glaucoma and no previous drainage surgery. There was a low incidence of serious side effects but nearly 60% were classified as failures by 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 9 publications
3
16
2
Order By: Relevance
“…However, due to limited length of follow-up and only 4 of 29 patients completed a 12-month follow-up, it would be difficult to make that conclusion without a larger sample size. ECP results have been variable, with some studies showing continued IOP lowering success for up to 2-3 years [6, 10, 25]. Perhaps our lower success rate over time could be attributed to our population which has a higher proportion of advanced and refractory glaucoma, and to our smaller ECP treatment zone.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, due to limited length of follow-up and only 4 of 29 patients completed a 12-month follow-up, it would be difficult to make that conclusion without a larger sample size. ECP results have been variable, with some studies showing continued IOP lowering success for up to 2-3 years [6, 10, 25]. Perhaps our lower success rate over time could be attributed to our population which has a higher proportion of advanced and refractory glaucoma, and to our smaller ECP treatment zone.…”
Section: Discussionmentioning
confidence: 90%
“…Francis et al [15] showed that ECP combined with phacoemulsification was more effective than cataract extraction alone to lower IOP and decrease IOP lowering medication dependence specifically in eyes with mild to moderate glaucoma previously controlled with IOP lowering medications. However, a recent study by Smith et al indicated that these results are temporary [10]. Lima et al [6] in a prospective study comparing ECP to AGV in patients with refractory glaucoma who were pseudophakic and had undergone trabeculectomy with antimetabolite previously, demonstrated that IOP lowering was similar between the two groups and the ECP group had less complications comparted to the AGV group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Smith et al 19 reported that IOP decreased from 18.7 mmHg preoperatively to 13.3 mmHg and 14.0 mmHg at 1 and 3 years postoperatively in a patient treated with phacoemulsification and ECP, respectively. Siegel et al 20 also reported an approximately 20% reduction in IOP at the 36month follow-up in patients treated with combined phacoemulsification and ECP.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed pre-and postoperative gonioscopic examinations identify the presence and extent of PAS and predict long-term IOP changes. Phaco/IOL combined with goniosynechialysis or endocyclophotocoagulation (ECP) may be considered in eyes with extensive PAS to achieve better IOP control [24][25][26].…”
Section: Kaplan-meier Survival Estimatesmentioning
confidence: 99%